Plasmon modes of bilayer molybdenum disulfide: a density functional study. (24th October 2017) - Torbatian, Z; Asgari, R
Abstract: We explore the collective electronic excitations of bilayer molybdenum disulfide (MoS2 ) using density functional theory together with random phase approximation. The many-body dielectric function and electron energy-loss spectra are calculated using an ab initio based model involving material-realistic physical properties. The electron energy-loss function of the bilayer MoS2 system is found to be sensitive to either electron or hole doping and this is due to the fact that the Kohn–Sham band dispersions are not symmetric for energies above and below the zero Fermi level. Three plasmon modes are predicted, a damped high-energy mode, one optical mode (in-phase mode) for which the plasmon dispersion exhibits q in the long wavelength limit originating from low-energy electron scattering and finally a highly damped acoustic mode (out-of-phase mode).